2006
DOI: 10.1111/j.1567-1364.2005.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopic study of the influence of physical stresses onSaccharomyces cerevisiaeandSchizosaccharomyces pombe

Abstract: Morphological changes in the cell surfaces of the budding yeast Saccharomyces cerevisiae (strain NCYC 1681), and the fission yeast Schizosaccharomyces pombe (strain DVPB 1354), in response to thermal and osmotic stresses, were investigated using an atomic force microscope. With this microscope imaging, together with measurements of culture viability and cell size, it was possible to relate topological changes of the cell surface at nanoscale with cellular stress physiology. As expected, when the yeasts were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 55 publications
1
37
1
4
Order By: Relevance
“…The reason why Adya et al . [27] did not find this morphological event in their heat shock study by AFM could be explained by the immobilisation technique these authors used, which likely destroyed the integrity of the cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason why Adya et al . [27] did not find this morphological event in their heat shock study by AFM could be explained by the immobilisation technique these authors used, which likely destroyed the integrity of the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Although AFM analysis of temperature stress on yeast cells has been previously addressed by Adya et al . [27], we have revisited this stress because of two major technical concerns in the study reported by the latter authors. Firstly, the immobilization procedure they used could likely alter the cell viability and integrity since yeast cells were immobilized on glass slides by air-drying for more than 5 hr.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscope (AFM) has emerged as a powerful tool for imaging biological samples at nanoscale without destroying the specimens. AFM has been used for characterizing the physical properties of microbial biofilms (Auerbach et al 2000), cell surface properties of fungi and bacteria (Adya et al 2006;Liu et al 2006), properties of microbial EPS (Taylor and Lower 2008), and single molecular recognition and interaction (Hinterdorfer and Dufrene 2006). Here, we extend the use of AFM to characterize the changes occurring on the surface of native unsaturated biofilms underwent different environmental stresses.…”
Section: Introductionmentioning
confidence: 97%
“…Saccharomyces cerevisiae, also called baker's yeast, is the best-characterized eukaryotic model for scientific and biomedical research. Although the chemical composition of the yeast cell wall is well known, its molecular ultrastructure (organization or assembly) has not been extensively studied at nanoscale (4,5), although there are a few reports on the nanomechanical and adhesive properties of the yeast cell wall under native conditions or under stress conditions (6)(7)(8). As for Candida albicans, it is by far the most common human-pathogenic fungal species.…”
mentioning
confidence: 99%